2-N-Arylthiazole inhibitors of Mycobacterium tuberculosis. Issue 17 (1st September 2017) - Clark, Michael P.; Wang, Tiansheng; Perola, Emanuele; Deininger, David D.; Zuccola, Harmon J.; Jones, Steven M.; Gao, Hong; VanderVen, Brian C.; Russell, David G.; Shoen, Carolyn M.; Cynamon, Michael H.; Thomson, John A.; et al.
Graphical abstract: Abstract: To develop agents for the treatment of infections caused by Mycobacterium tuberculosis, a novel phenotypic screen was undertaken that identified a series of 2- N -aryl thiazole-based inhibitors of intracellular Mycobacterium tuberculosis . Analogs were optimized to improve potency against an attenuated BSL2 H37Ra laboratory strain cultivated in human macrophage cells in vitro . The insertion of a carboxylic acid functionality resulted in compounds that retained potency and greatly improved microsomal stability. However, the strong potency trends we observed in the attenuated H37Ra strain were inconsistent with the potency observed for virulent strains in vitro and in vivo .